Rosetta: Standardization at the System Level. - Alexander, Perry (Computer (00189162), 2009)
This article discusses the development of the Rosetta programming language for use in the system-level design of electronics. The elaboration of the semantics of this language by the Institute of Electrical and Electronic Engineers Inc. Computer Society (IEEE) P1699 Rosetta Working Group is described. The challenges of incorporating information on performance constraints and heterogeneous domain characteristics in the development of so-called system-on-chips (SoCs) are described. The characteristics of Rosetta, which is a heterogeneous, declarative, and formal language for engineering SoCs is noted. The development of the facet and domain based definition systems for this language is explored.